The Effect of Leverage and Profitability on Company Value with Managerial Ownership as A Moderator - Amanda, Lisani; Wulandari, Tari; Komara, Acep (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The current research looks at how profitability and leverage affect a company's value, taking managerial ownership into account as a moderating factor. Manufacturing companies in the subsector of garments and textiles that are listed on the Indonesia Stock Exchange were the study's primary focus. The use of secondary data from company financial reporting. Purposive sampling was used for the sample process. Design/methodology/approach: Analytical methods used include descriptive statistical analysis, multiple linear regression analysis, and moderated regression analysis (MRA). Findings: The test findings demonstrate that the independent variables alone are unable to affect the dependent variable. Additionally, the moderating variable has not been demonstrated to effectively moderate how the independent factors affect the dependent variable. Research limitations/implications: Companies that manufacture clothing and textiles and were listed on the Indonesia Stock Exchange between 2019 and 2022 are the subject of this study. The results of this investigation might not be applicable to other sectors or eras. Practical implications: Investors can use the results of this study to help make financial decisions and by management in managing leverage and profitability. Originality/value: The author makes truth and originality the foundation of their work. Paper type: Research paper.